ALOHA Simulation to Determine Consequence Scenarios on Transportation Liquefied Natural Gas (LNG) in DKI Jakarta Province - Dody Guntama; Ayu Lintang Cahyani; Vidrika Linda; Sari Sekar Ningrum (Journal of Community Based Environmental Engineering and Management, 2022)
The mobility of using LNG is based on its advantages as a substituent fuel for gasoline and diesel, where LNG has low emission properties. The process of mobilizing the distribution of LNG has the potential for accidents when it takes place. The study was conducted to determine the hazards that can occur and the safe distance for evacuation in the event of a leak using ALOHA simulation. The research process is carried out by studying literature, collecting data, determining the month and time of release, and continuing with a simulation of the existing data. The data analysis technique was carried out by determining the tank temperature and water dispersion model at 31 SPBG. Fireball simulation results at 8:00 a.m. 2:00 p.m, and 10:00 p.m have safe distances at 812 meters, 812 meters, and 815 meters. Fire column simulation results at 8:00 a.m. 2:00 p.m, and 10:00 p.m have safe distances at 29 meters, 29 meters, and 28 meters. Vapor cloud simulation results at 8:00 a.m. 2:00 p.m, and 10:00 p.m have Lower Explosive Limits (LEL) at 169 meters, 160 meters, and 243 meters. Thus the ALOHA simulation can represent the safe distance of evacuation and scenarios in the event of an accident.